Startup and burnup strategy for Th–U/U–Pu fuel cycles in an EM2 reactor. (November 2015) - Ma, Y.W.; Li, X.X.; Cai, X.Z.; Yu, C.G.; Zou, C.Y.; Han, J.L.; Chen, J.G.
Abstract: General Atomics (GA) is developing the Energy Multiplier Module (EM 2 ) which is a compact gas-cooled fast reactor as one of candidates of the Generation-IV nuclear energy systems. In the EM 2 core, low enriched uranium is used as igniting fuel and depleted uranium is used for converting and burning. It indicates that EM 2 can maintain critical operation for more than 30 years without refueling. To further study the Th–U fuel cycle performance in the EM 2, two kinds of start-up strategies with Th–U (Th + 233 U) and semi Th–U (Th + enriched 235 U) are evaluated. Neutronics characteristics, such as the effective multiplicity factor ( k eff ) and conversion ratio (CR) are analyzed from neutron usage point of view. The simulated results for the two kinds of fuels are compared with the U–Pu fuel from the design of GA. The analysis gives an insight into the pros and cons of U–Pu and Th–U fuel cycles in terms of the breeding capability and the discharged radio-toxicity. The breeding performance of the second generation EM 2 is also presented and compared with that of the first generation EM 2 . It indicates that the multi-generation EM 2 can deepen the burnup and reduce the waste management pressure for each kind of fuel loading strategy. Highlights: The neutronics based on U–Pu, Th–U and semi Th–U fuel cycle are studied in EM 2 . The U5–Th fuel loading is a better option from the viewpoint of reactor lifetime and initial reactivity control. Introduction of the multi-generation EM 2 can significantly deepen the burn-up and reduce the waste management pressure.